Policy Implementation Analysis on the Utilization of General Practitioners at Community Health Centers in Kemayoran From January 2013 to June 2014 - Padmasari, Indah Raksi; Megraini, Amila (Journal of Indonesian Health Policy and Administration, 2015)
Community Health Centers (CHCs) take the frontline position of health services in Indonesia. To be able to perform their functions properly, CHCs require human resources (HR) as a driving force. One of the human resources required is a general practitioner. The policy of utilization GP sat CHCs in Jakarta provides flexibility for sub-district health centers as the implementing agency in the management of human resources. One of the variables that influence the process of policy implementation is the capability of the implementing agencies indicated through their management capabilities. This study aims to describe the policy implementation on the utilization of general practitioners at Kemayoran sub- district health centers. The research was conducted using a mixed method combining qualitative and quantitative approach. The results confirm that there has been an imbalance proportion between the workload of general practitioners at village health centers and sub-district health centers, due to the absence of standardized rules regarding the placement of general practitioners, in addition to lower capacity of the human resources available. One of the recommendations proposed is the improvement of management using a simulation model of general practitioners based on balanced workload forecasting.